"Training for all" calls for a pedagogy of diversity - Bylinski, Ursula [Verfasser]; Rützel, Josef [Verfasser] (My University, 2013)
"The aim behind the principle of 'training for all' is to enable all young people to achieve integra tion into employment and society through an initial vocational qualification in a skilled occupation. It is the vision of inclusive education to give all young people access to high-quality education, putting everyone in a position to develop his or her potential. In the UNESCO 'Education for All' programme this is formulated as a universal aspiration, irrespective of a person’s gender, social and economic conditions or particular learning needs. This article looks at which steps have been taken, what has been achieved so far and where further action is needed in order to progress towards this goal. It also asks how important the concept of inclusion is for the assistance of disadvantaged individuals in the vocational training system." (Autorenreferat, BIBB-Doku)
Keywords: P 1.7 Benachteiligte; G 1.3.2.2 Übergänge; Benachteiligtenförderung; Übergangssystem; Inklusion